THE QUALITY OF PEER RELATIONS IN A SCHOOL ENVIRONMENT: FROM INDIFFERENCE TO MUTUAL SUPPORT - Iłendo-Milewska, Agnieszka; Nawrocka, Joanna (PEOPLE: International Journal of Social Sciences, 2018)
The quality of peer relationships is one of the traditional issues of social psychology. Extensive knowledge of this area enables us to deeper the understanding of different types of conflicts among peers, but does not allow their effective prevention. This research sought to investigate the students’ perception of peer relation and estimate behavioral tendency related to the psychological theory. The article is based on the humanistic conception of students’ support as well as the Stereotype Content Model (SCM), the BIAS Map (Fiske et al., 2002; 2007) and the Integrated Threat Theory (Stephan, 2002). To measure the aspects of the quality of peer relations, three questionnaire were used: the Semantic Differential Technique ’Typical Peer’ (A. Iłendo-Milewska, 2007), the Data Sheet to evaluate the behavioral tendency and to recognize the emotion (A. Iłendo-Milewska, 2013), and the Scale of Social Support by Roman Cieślak (1995) to measure the mutual support in students’ perception. The results present two main themes in the field of the quality of peer relation: (1) the students in the 1st grade experienced unpleasant emotions towards a typical peer and they perceived ’a typical peer’ as less competent than students in the 3nd grade, (2) in the area of currently received support, the group of 1st grade students significantly more often declares that a typical peer did not show the understanding for the school situation. The results help understand that the intervention programs should be implemented in order to shape the deeper level of peer relation in the school environment.